2010
DOI: 10.1111/j.1440-1681.2009.05292.x
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin receptor contributes to diabetic nephropathy by enhancing renal inflammation

Abstract: SUMMARY (Pro)renin receptor (PRR) binding to renin or prorenin mediates Ang II dependent and independent effects. PRR expression was increased in the kidneys of diabetic rats but its role in diabetic nephropathy is unknown. We investigated the contribution of PRR to the development of diabetic nephropathy through enhancement of renal production of tumor necrosis factor-α (TNF-α) and interleukine-1β (IL-1β).Normoglicemic control and streptozotocin-induced diabetes Sprague-Dawley rats were studied. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 37 publications
6
94
1
Order By: Relevance
“…Thus, receptor-bound prorenin may be elevated by an increase in prorenin levels and/or an increase in (P)RR levels, 13 thereby contributing to the development of nephropathy in diabetic animals. These findings were recently confirmed by Matavelli et al 14 The direct administration of HRP to the renal cortical interstitium of diabetic rats significantly decreased urinary albumin excretion and the renal production of tumor necrosis factora and interleukin-1b. A similar improvement in nephropathy after HRP treatment was observed in streptozotocin-induced diabetic rats in which nephropathy had already developed 15 and in angiotensin IItype Ia-receptor-deficient mice with streptozotocin-induced diabetes.…”
Section: Suggestions From Animal Models Of Diabetessupporting
confidence: 74%
“…Thus, receptor-bound prorenin may be elevated by an increase in prorenin levels and/or an increase in (P)RR levels, 13 thereby contributing to the development of nephropathy in diabetic animals. These findings were recently confirmed by Matavelli et al 14 The direct administration of HRP to the renal cortical interstitium of diabetic rats significantly decreased urinary albumin excretion and the renal production of tumor necrosis factora and interleukin-1b. A similar improvement in nephropathy after HRP treatment was observed in streptozotocin-induced diabetic rats in which nephropathy had already developed 15 and in angiotensin IItype Ia-receptor-deficient mice with streptozotocin-induced diabetes.…”
Section: Suggestions From Animal Models Of Diabetessupporting
confidence: 74%
“…Additionally, several clinical and animal studies have indicated that inflammatory cytokines play an important role in the development and progression of diabetic nephropathy (29,30). It was demonstrated that diabetes increased proinflammatory renal production, including TNF-α, IL-1β and IL-6 in the circulating, and urinary excretion (31)(32)(33). Another important finding in the current study is that the levels of MDA and protein carbonyl group and protein expression of MnSOD and CuZn-SOD in renal tissues as well as TNF-α, IL-1β and IL-6 in plasma were remarkably increased in the vehicle and diabetic groups compared to non-diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…An upregulation in (pro)renin and (P)RR levels contributing to the development of nephropathy in diabetic animals has been reported by many investigators (reviewed in Balakumar and Jagadeesh 26 ). Recently, Matavelli et al 95 extended these mechanisms suggesting that the renal (pro)renin and (P)RR axis promotes diabetic nephropathy by significantly increasing the amounts of pro-inflammatory cytokines. The handle region peptide (HRP), a putative blocker of the (P)RR, could efficiently block glomerulosclerosis, 86,88,95,96 while RAS inhibitors were unable to prevent end-stage organ damage associated with diabetes.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 98%
“…Recently, Matavelli et al 95 extended these mechanisms suggesting that the renal (pro)renin and (P)RR axis promotes diabetic nephropathy by significantly increasing the amounts of pro-inflammatory cytokines. The handle region peptide (HRP), a putative blocker of the (P)RR, could efficiently block glomerulosclerosis, 86,88,95,96 while RAS inhibitors were unable to prevent end-stage organ damage associated with diabetes. 97,98 However, not all investigators were able to reproduce the inhibitory effects of HRP either in vivo or in vitro.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 98%